Do LLMs dream of antique hermeneutics? : Critical remarks on automated text interpretation - Dörpinghaus, Jens [Verfasser]; Tiemann, Michael [Verfasser] (My University, 2025)
"This study investigates the potential of large language models (LLMs) to apply hermeneutical methods rooted in philosophy, theology, sociology and literary studies in a meaningful manner. Utilising a comparative experimental design, four LLMs were prompted to interpret a variety of texts, encompassing religious, philosophical, poetic, and conversational material. The findings indicate considerable variability, an absence of reproducibility, and a substantial reliance on prompt design, model type, and language. This suggests that LLMs do not employ coherent hermeneutical strategies. Despite the automation of formal features, limitations in context sensitivity, interpretive intentionality, and epistemic grounding render LLMs ill-suited to authentic hermeneutics. The study concludes that current LLMs are incapable of replicating the depth of human interpretive practice, and calls for further interdisciplinary research to define evaluation standards for machine-assisted exegesis." (Authors' abstract, BIBB-Doku)
Keywords: T 3 Forschungsmethoden; 370; Datenanalyse; Automatisierung; Künstliche Intelligenz; Hermeneutik; Interdisziplinäre Forschung